Bahasa Inggris - Ni Nyoman Sri Cintya Parmita; I Gusti Ayu Vina Widiadnya Putri (Language and Education Journal Undiksha, 2023)
This study aimed to identify if visitors to Garuda Wisnu Kencana Cultural Park used positive politeness strategies. The theory of Brown and Levinson (1987) regarding the various politeness techniques was employed in this study as the basis for a descriptive qualitative method to depict the data. According to theory, only six of the six sub-strategies in positive politeness were used by the visitor when giving a review: (1) Exaggerate (interest, approval, sympathy with H), (2) Intensify Interest to H, (3) Seek Agreement, (4) Offer Promise, (5) Give or Ask Reason, and (6) Give Gifts to H Goods, Sympathy, Understanding, and Cooperation. As a result, the visitor employs a gracious approach to express their feelings while visiting Garuda Wisnu Kencana Cultural Park.